L’utilisation des images satellitaires dans la détermination des facteurs de dégradation des écosystèmes agricoles (Facteur de l’étalement urbain) - Makrerougrass, Zohra (My University, 2016)
Renewable natural resources in our country are currently threatened with extinction under the combined effect of human activities and climate change. The land use change are key factors for sustainable development. The contribution of satellite images in detecting land cover change through the use of remote sensing and geographic information system has enabled us to make a diachronic study from the treatments carried out on a series of satellite images of Landsat 4 TM 1987 and ETM + image of Lndsat 5 ETM + 2010 to see the degradation of natural environments in the semi-arid to detect changes in land use that affect our study area (Relizane) This study aims to highlight the nature and extent of the factors and parameters that contribute to the degradation of renewable natural resources at the Relizane, subject to anthropogenic and climatic pressures, constituting a direct threat to the renewal of these resources in the study area. The results of treatment of the satellite images clearly show that there is a large area of agricultural land lost or degraded by the phenomenon of urban sprawl.
Keywords: degradation; natural resources; urban sprawl; Relizane; dégradation; ressources naturelles; l’étalement urbain; Relizane